Analysis of Inheritance Law Regarding Inheritance Disputes in the Decision of the Supreme Court of the Republic of Indonesia Number 793 k/Ag/ 2018 - Rolib Sitorus; Jerry Merkury (Journal of Legal and Cultural Analytics, 2025)
Inheritance law covers the transfer or assignment of a person's assets to the procedures for their distribution and settlement as stated in the Decision of the Supreme Court of the Republic of Indonesia Number 793 K/Ag/2018. In this writing, the research was conducted to determine the legal position of the plaintiff and defendant regarding the distribution of inheritance and to determine how the legal protection for the defendants regarding the ownership of inherited assets in the case of the distribution of inheritance assets in the Decision of the Supreme Court of the Republic of Indonesia Number 793 K/Ag/2018. The legal research method used in this research is normative legal research which is research that is conducted or aimed only at written regulations with a literature study method. which functions to describe or provide an overview of the object being studied. The data source used is secondary data with qualitative data analysis. The legal position of the Plaintiff Drs Sangkala Msi is the first class heir from his parents, namely Pamaling bin Tala and Debo binti naro, which is based on Article 174 paragraph (1) of the KHI is a son. The legal position of the Defendant Nurbaya binti Basang and Ahmad bin Jumasang is a substitute heir. Article 185 of the KHI states that the heirs who die rather than the testator's position can be replaced by their children. The legal position of the plaintiff and defendant is regulated in Article 171 of the KHI which regulates that the heirs are blood relatives or marital relations with the testator, are Muslim and are not prevented by law from becoming heirs.